Exploring Undergraduate Medical Students’ Perceptions and Career Choices in Obstetrics and Gynecology - Duhm, Lina; Wittek, Agnes; Plöger, Ruben; Haverkamp, Nicolas; Marinova, Milka; Strizek, Brigitte; Recker, Florian (Geburtshilfe und Frauenheilkunde, 2025)
There is a global shortage of obstetricians and gynecologists (OB/GYN), raising concerns about patient care and workforce sustainability. Germany faces a particularly acute shortage, exacerbated by the impending retirement of many senior consultants. This study explores the career perceptions of graduate-entry medical students at the University of Bonn, focusing on their attitudes toward a career in OB/GYN.A cohort of fifth year medical students (n = 213) participated in this study. Surveys were administered directly via QR codes at two points in the 10th semester: pre-rotation (pre-clerkship) and post-rotation, at the time of the OSCE (OSCE = objective structured clinical examination) in OB/GYN. The questionnaires assessed multiple dimensions of students’ career preferences, understanding of the specialty, and the impact of clinical exposure on their perceptions. Statistical analyses, including McNemar’s test, were performed to evaluate changes in students’ perspectives.The findings revealed that prior to clinical exposure, only 32% of students expressed interest in a career in OB/GYN. After completing the rotation, this interest remained unchanged. Notably, concerns about night shifts increased significantly post-rotation, with 75% of students citing it as a key deterrent. Furthermore, financial considerations gained importance, with 54% of students highlighting future income as a critical factor post-rotation compared to 43% pre-rotation. Despite improved understanding of OB/GYN following hands-on experience, concerns about workload and stress persisted.While clinical exposure increased students’ knowledge of OB/GYN, it did not significantly affect their interest in the specialty, likely due to concerns about work-life balance and the demanding nature of the field. The study underscores the need for reforms in OB/GYN training and practice environments to address these deterrents and improve recruitment into this essential specialty.
Keywords: education; undergraduate education; medical students; career choice; obstetrics; gynecology